Critical thinking a user's manual - Jackson, Debra (Wadsworth / Cengage Learning, 2012)
CRITICAL THINKING: A USER'S MANUAL offers an innovative skill-based approach to critical thinking that provides step-by-step tools for examining arguments. Students build a complete skill set by recognizing, analyzing, diagramming, and evaluating arguments; later chapters encourage application of the basic skills to categorical, truth-functional, analogical, generalization, and causal arguments as well as fallacies. The exercises throughout the text engage readers in active learning, integrate writing as part of the critical thinking process, and emphasize skill transference. A special feature, called Your Turn! encourages students to not just skim through the book's explanations, but stop, think, and apply what they are learning.